A systematic review and meta-analysis of the executive function-health behaviour relationship. Issue 1 (1st January 2019) - Gray-Burrows, Kara; Taylor, Natalie; O'Connor, Daryl; Sutherland, Ed; Stoet, Gijsbert; Conner, Mark
ABSTRACT: Objective: This study provides the first comprehensive meta-analysis of the relationship between executive function (EF) and performance of health behaviours in healthy populations. Method: Electronic databases (MEDLINE, Embase, PsycINFO, Web of Science) were searched, and forward and backward citation tracking was undertaken to identify articles investigating the relationship between EF and health behaviour. Studies were eligible if they examined the direct correlational relationship between EF and health behaviour in healthy populations, were available in English and published in peer-reviewed journals in any year. Results: Sixty-one articles covering 65 tests were included in a random effects meta-analysis. Several moderators were assessed, including: the type, and addictiveness of the health behaviour; the type of EF measure; study design, and sample characteristics. Overall EF had a significant, but small correlation with health behaviour; EF was significantly positively associated with health-protective behaviours and significantly negatively associated with health-damaging behaviours. There was considerable heterogeneity in the observed effect sizes, but this was not explained by the examined moderators. Conclusions: Although the meta-analysis indicates a significant effect for EF on health behaviour, effect size is small. Due to the complex nature of EF, more research is required to further elucidate the relationship between EF and health behaviour in its entire conceptualization.